2021
DOI: 10.1007/s13369-021-06240-z
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Detection of COVID-19 from CT Images Based on Gaussian Mixture Model and Kernel Support Vector Machines Classifier

Abstract: COVID-19 is a virus that has been declared an epidemic by the world health organization and causes more than 2 million deaths in the world. To achieve this, computer-aided automatic diagnosis systems are created on medical images. In this study, an image processing and machine learning-based method is proposed that enables segmenting of CT images taken from COVID-19 patients and automatic detection of the virus through the segmented images. The main purpose of the study is to automatically diagnose the COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…For example, both the modified AlexNet and GoogLeNet obtain the same state-of-the-art performance with a classification accuracy of 98.39%, a sensitivity of 98.97%, a specificity of 96.67%, and Matthew correlation coefficient of 99.11%. Saygl proposed a method based on image processing and machine learning to automatically detect viruses through segmented CT images with optimal accuracy values of 98.5% in dataset 1, 86.3% in dataset 2, and 94.5% in mixed dataset [ 18 ]. The screening results of other algorithms also remarkably outperform 90% on all the metrics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, both the modified AlexNet and GoogLeNet obtain the same state-of-the-art performance with a classification accuracy of 98.39%, a sensitivity of 98.97%, a specificity of 96.67%, and Matthew correlation coefficient of 99.11%. Saygl proposed a method based on image processing and machine learning to automatically detect viruses through segmented CT images with optimal accuracy values of 98.5% in dataset 1, 86.3% in dataset 2, and 94.5% in mixed dataset [ 18 ]. The screening results of other algorithms also remarkably outperform 90% on all the metrics.…”
Section: Resultsmentioning
confidence: 99%
“…In practice, a new supplementary examination approach is demanding to improve the screening accuracy and reduce the radiation dose. While a few recent studies on automated COVID-19 screening have made great progress, they only focus on designing either chest CT-based approaches or Xray-based techniques [1,2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Both chest CT and X-ray are common medical imaging methods in clinical but have three-fold limitations in the task of automated screening of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that IoT-based technology and modified techniques for taking out the background worked well together. By applying GMM Filter [22,23] to reduce unwanted small items, this research completes and continues object detection on video.…”
Section: Introductionmentioning
confidence: 85%
“…The GMM is a very popular unsupervised learning technique. This technique is popular to be used to form new synthetic data on small-sized datasets [17], [18], [19], [20]- [24]. Moreover, the GMM has been widely successfully applied in the prediction system on medical-related topics such as predicting COVID-19 cases [22], liver cancer detection [25], pancreatic cancer detection [26], medical image segmentation [27], and texture characterization of brain DTI image [28].…”
Section: B Feature Selection and Data Augmentationmentioning
confidence: 99%